An Integrated Pharmacokinetic Study of an Acanthopanax senticosus Extract Preparation by Combination of Virtual Screening, Systems Pharmacology, and Multi-Component Pharmacokinetics in Rats - Shi, Peiying; Xie, Yunjiao; Xie, Rongfang; Lin, Zuan; Yao, Hong; Wu, Shuang (Frontiers in Pharmacology, 2020)
In this paper, the integrated pharmacokinetics (PK) of an Acanthopanax senticosus extract preparation (ASEP, named as Ciwujia injection in clinic in China) was explored by combining with multi-component PK in rats, virtual screening, systems pharmacology and molecular docking. Firstly, the ingredients in ASEP with high contents and detectable property in rat plasma was selected. Next, the PK study of the resulted ingredients was performed in rats (1.76 mL/kg and 3.52 mL/kg of 5 times concentrated ASEP, single i.v.). Meanwhile, the drug targets for the ingredients screen out were predicted by using a target fishing online server, PharmMapper (http://www.lilab-ecust.cn/pharmmapper/) with a fit filtration threshold of z'-score >0. Next, the network pharmacology, molecular docking, diseases ontology (DO) analysis, and Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis were performed respectively for the predicted targets. Finally, the supporting evidences were obtained to characterize the PK markers and carry out the integrated PK study with “plasma-drug concentration sum” or “plasma-drug AUC weighted” methods. As a result, 6 ingredients, involving 5-caffeoylquinic acid (5-CQA), 3-CQA, 4-CQA, protocatechuic acid, eleutheroside B and gentiopicroside were selected, and their PK profiles were elucidated. The 6 ingredients were highly related to arteriosclerotic cardiovascular disease and atherosclerosis and could mainly interact with similar targets e.g. GSK3B, PDPK1, PLAU, etc., or pathways e.g. Insulin, VEGF, FoxO, etc, providing the basis for integrating plasma drug concentration. Ultimately, the 6 ingredients were considered as PK markers and the whole in vivo process of ASEP were characterized. Our study would enhance understanding of the therapeutic effects and mechanisms of ASEP against cardiovascular diseases, and provided useful insights for future integrated PK study on anti-cardiovascular diseases TCM injections.